2015
DOI: 10.3390/rs8010018
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology, Dynamics and Potential Hotspots of Land Surface Temperature at a Local Scale in Urban Areas

Abstract: Current characterization of the Urban Heat Island (UHI) remains insufficient to support the effective mitigation and adaptation of increasing temperatures in urban areas. Planning and design strategies are restricted to the investigation of temperature anomalies at a city scale. By focusing on Land Surface Temperature of Wuhan, China, this research examines the temperature variations locally where mitigation and adaptation would be more feasible. It shows how local temperature anomalies can be identified morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 49 publications
2
41
0
Order By: Relevance
“…The green space distribution can be seen in Figure 1. Within 500 m, urban green space plays an important role in cooling the surrounding environment [31]. Thus, this work selected the remote sensing image information space with a precision of 30 m × 30 m and set up 17 buffer zones within 500 m to conduct analysis and research ( Figure 2).…”
Section: Selection Of Green Space and Buffer Settingmentioning
confidence: 99%
“…The green space distribution can be seen in Figure 1. Within 500 m, urban green space plays an important role in cooling the surrounding environment [31]. Thus, this work selected the remote sensing image information space with a precision of 30 m × 30 m and set up 17 buffer zones within 500 m to conduct analysis and research ( Figure 2).…”
Section: Selection Of Green Space and Buffer Settingmentioning
confidence: 99%
“…Previous studies have mainly focused on studying differences in ground temperatures as a function of land-use land cover and its evolution at the city level [16,16,20,[33][34][35], temporal trends in urban SUHI in urban areas [18,36,37], the refreshing impact of parks on their surroundings [15,38,39], the evolution of SUHI as a function of day and night [9,34,40,41], the impact of vegetation on LST at the urban scale [12,36,37,42], comparison of surface temperatures and air temperature [8][9][10]20,43,44], the impact of surface temperatures on health [30,41] and transversely at surface temperatures at moderate resolutions (MODIS 1 km) [16,20,[34][35][36]42,45] but, to our knowledge, there are no similar studies such as ours that analyze the thermal monitoring of site redevelopment at such a detailed spatial and temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…However, the parameters to characterize the spatio-temporal patterns of LST are limited [1,31,32], although sufficient parameters are available for UHI study such as magnitude or intensity, spatial extent, position, and orientation. Since research in geography has suggested that continuous and smooth surface supports pattern recognition more effectively [33,34], the parameterized surface models [35][36][37] and non-parametric kernel models [31,38,39] were utilized to quantify thermal characteristics and generate parameters from a smoother surface. Among them, Wang et al [31] introduced the latent pattern of LST (LLST) and a morphological parameter named the Multi-scale Shape Index (MSSI) to the urban climate community to enrich the parameter system of LST pattern mining.…”
Section: Introductionmentioning
confidence: 99%